An Autoethnographic Visitor: Liminal Interrogations of Lessons from the Steps of the Union. Issue 4 (February 2015) - Brogden, Lace Marie
Using "perspectives" from la bande-dessinée, this writing positions the International Congress of Qualitative Inquiry as a site of inquiry for querying autoethnographic possibilities of being as/and theory. Drawing on Urbana/South Florida interpretations of autoethnography as method, it combines contributions from French philosophers (Cixous, Deleuze, Derrida, et autres ) and ICQI boundary pushers (Rolling, Weems, Wyatt, and others) to story research/border crossing/writing in view of postcetera academic subjectivities.